Mechanistic correlations between two itch biomarkers, cytokine interleukin-31 and neuropeptide β-endorphin, via STAT3/calcium axis in atopic dermatitis - Lee, C.-H.; Hong, C.-H.; Yu, W.-T.; Chuang, H.-Y.; Huang, S.-K.; Chen, G.-S.; Yoshioka, T.; Sakata, M.; Liao, W.-T.; Ko, Y.-C.; Yu, H.-S. (British journal of dermatology (1951), 2012)
Summary Background  Itch is the cardinal symptom of atopic dermatitis (AD). β‐Endorphin, a neuropeptide, is increased in both AD skin and sera. Interleukin (IL)‐31, an itch‐relevant cytokine, activates IL‐31 receptors in keratinocytes. However, how IL‐31 and β‐endorphin interact in AD skin remains elusive. Objectives  To investigate the mechanistic interaction of IL‐31 and β‐endorphin in AD. Methods  This was a prospective cross‐sectional study. We recruited adult patients with AD and controls according to Hanifin’s AD criteria. Serum levels of IL‐31 and β‐endorphin were measured by enzyme‐linked immunosorbent assay. Expressions of IL‐31 receptor A (IL‐31RA) and β‐endorphin in the skin were assessed by immunohistochemistry. Their expression in the skin and blood was compared and correlated in patients with AD and in controls. We also treated primary keratinocytes with IL‐31 and measured calcium influx, β‐endorphin production and signalling pathways to define their mechanistic interactions. Results  β‐Endorphin was increased in the supernatant from IL‐31‐treated keratinocytes. IL‐31 receptor activation resulted in calcium influx and STAT3 activation; pretreatment with STAT3 inhibitor stopped the increase of β‐endorphin. Notably, either replacement of extracellular calcium or treatment with 2‐aminoethoxydiphenyl borate, an inhibitor for the store‐operated channel, blocked STAT3 activation. We found higher levels of blood β‐endorphin and IL‐31, which were significantly correlated, in patients with AD. Moreover, IL‐31RA and β‐endorphin were increased and colocalized both in AD human skin and TPA‐painted mouse skin. Conclusions  IL‐31 receptor activation in keratinocytes induces calcium influx and STAT3‐dependent production of β‐endorphin. These results might contribute to an understanding of the regulatory mechanisms underlying peripheral itch.